A magnetic heterocyclic amine molecular imprinting composite material and its preparation method and application
By covering the polymer of heterocyclic amine template molecularly imprinted by the magnetic particle core surface and chemically bonding hydrophilic polymer segments, the problem of reduced molecular recognition performance of molecular imprinted materials in aqueous media is solved, and high selective adsorption and separation are achieved, which is suitable for heterocyclic amine analysis in biological samples.
Patent Information
- Application Number
- CN202210555798.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-19
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2042-05-19
AI Technical Summary
The molecular recognition performance of existing molecular imprinting materials in aqueous media is significantly reduced, limiting their application in biological samples.
By coating the polymer shell with heterocyclic amine template molecules on the surface of the core of the magnetic particles, and chemically bonding hydrophilic polymer segments on the surface of the shell, the adsorption selectivity of the material in an aqueous medium is improved by utilizing the hydrophilic and chargeable effects of the carboxyl and/or hydroxyl groups.
High selective adsorption and separation of heterocyclic amines in aqueous media are achieved, and the defect of significantly reduced adsorption performance of general molecular imprinting materials in aqueous systems is overcome, and the characteristics of easy separation are obtained.
Smart Images

Figure BDA0003652238990000101 
Figure BDA0003652238990000111
Abstract
Description
Technical Field
[0001] The invention relates to a magnetic heterocyclic amine molecular imprinting composite material and a preparation method and application thereof, belonging to the field of polymer materials. Background Art
[0002] Molecularly imprinted polymers are highly cross-linked three-dimensional polymer networks that can memorize the shape and functional groups of template molecules. Molecularly imprinted polymers have the advantages of simple preparation process, good heat resistance and chemical stability, and high selectivity and recognition of template molecules. They are widely used in solid phase extraction, chromatographic separation, chemical bionic sensors, enzyme catalysis, drug delivery and other fields.
[0003] Magnetic materials have superparamagnetism and can be easily separated from the medium using an external magnetic field. Therefore, they are a sample pretreatment separation material with excellent application effects. By modifying the surface of magnetic materials, various functional groups and functional sites can be introduced on their surfaces to achieve efficient enrichment and rapid separation of target compounds. The combination of magnetic materials and molecular imprinting materials has the characteristics of selective adsorption of molecular imprinting materials and the easy separation characteristics of magnetic materials, which can greatly simplify the enrichment and separation process of target compounds in complex media.
[0004] Heterocyclic amines are a class of polycyclic aromatic compounds containing nitrogen heterocycles, which are usually highly carcinogenic and mutagenic. The contamination of food by heterocyclic amines and the health hazards caused by them have become one of the hot issues in the field of food safety and risk assessment. The main exposure routes of human body to heterocyclic amines are eating fried meat and exposure to cigarette smoke. The heterocyclic amines that are currently receiving more attention include 2-amino-3-methylimidazo[4,5-f]quinoline (IQ), 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP), 2-amino-3,8-dimethylimidazoquinoxaline (MeIQx), 1-methyl-9H-pyrido[3,4-b]indole (Harman), 9H-pyrido[3,4-b]indole (Norharman), 2-amino-9H-pyrido[2,3-b]indole (AαC), 2-amino-3-methyl-9H-pyrido[2,3-b]indole (MeAαC), etc. Among them, IQ, PhIP and MeIQx are found in higher levels in meat products, while the heterocyclic amines in cigarette smoke are mainly Harman, Norharman, AαC and MeAαC. When analyzing heterocyclic amines in biological samples such as urine and blood, complex sample pretreatment is usually required due to the complexity of the matrix, severe matrix interference, and extremely low levels of heterocyclic amines. However, these pretreatment processes are cumbersome, time-consuming, and labor-intensive. It is difficult and challenging to detect heterocyclic amines in biological samples such as urine and blood using traditional methods.
[0005] In order to more conveniently separate and enrich heterocyclic amines in biological samples, Chinese patent document CN103467654A discloses a magnetic heterocyclic amine molecular imprinted polymer, which uses Fe3O4 nanoparticles as core, and the molecular imprinted material is wrapped outside the core. The molecular imprinted material uses heterocyclic amine as a template molecule, methacrylic acid as a functional monomer, trimethoxypropane trimethacrylate and divinylbenzene as crosslinking agents, and azobisisobutyronitrile as an initiator. When the magnetic heterocyclic amine molecular imprinted polymer is used for adsorption and separation of heterocyclic amines in an organic phase, it has the advantages of high selectivity, large adsorption capacity, fast separation speed, and strong anti-interference ability. However, the heterocyclic amines in biological samples (such as urine, blood, etc.) are usually in aqueous media, but the molecular imprinted polymer has significantly reduced molecular recognition performance in aqueous media, especially complex aqueous media, which seriously limits their wide application in aqueous media. Therefore, it is of great significance to develop imprinted materials suitable for adsorption of heterocyclic amines in aqueous systems (such as biological samples) for the analysis and detection of heterocyclic amines. Summary of the invention
[0006] The object of the present invention is to provide a magnetic heterocyclic amine molecular imprinting composite material which can be used for adsorbing heterocyclic amine in aqueous medium.
[0007] The second object of the present invention is to provide a method for preparing a magnetic heterocyclic amine molecular imprinted composite material.
[0008] The third object of the present invention is to provide an application of a magnetic heterocyclic amine molecular imprinting composite material in adsorbing heterocyclic amines in an aqueous system.
[0009] In order to achieve the above objectives, the technical solution adopted by the magnetic heterocyclic amine molecular imprinted composite material of the present invention is:
[0010] A magnetic heterocyclic amine molecular imprinting composite material comprises a magnetic particle core and a heterocyclic amine template molecular imprinting polymer shell coated on the surface of the magnetic particle core, wherein the surface of the molecular imprinting polymer shell is chemically bonded with a hydrophilic polymer segment, and the hydrophilic group in the hydrophilic polymer segment is a carboxyl group and / or a hydroxyl group.
[0011] The magnetic heterocyclic amine molecular imprinting composite material of the present invention has magnetic particles as the core, and the core is coated with a heterocyclic amine template molecular imprinting polymer shell, and the imprinting sites in the shell provide high selectivity and high adsorption capacity for the adsorption of heterocyclic amines. Since the surface of the shell is chemically bonded with a hydrophilic polymer chain segment with carboxyl and / or hydroxyl as the hydrophilic group, the hydrophilicity and charge of the carboxyl and / or hydroxyl groups can effectively resist the non-selective adsorption and interference of interfering substances (such as proteins, etc.) in aqueous complex media, thereby improving the adsorption selectivity of the magnetic heterocyclic amine molecular imprinting composite material in aqueous media, thereby effectively overcoming the defect that the adsorption performance of general molecular imprinting materials in aqueous systems is greatly reduced, and expanding the application range of molecular imprinting materials. Since the magnetic heterocyclic amine molecular imprinting composite material of the present invention contains magnetic particles, after the adsorption of heterocyclic amines in aqueous media is completed, simple and rapid separation can be achieved through magnetic substances.
[0012] Preferably, the hydrophilic polymer segment is formed by polymerization reaction using methacryloylglycylglycine and / or hydroxyethyl methacrylate as polymerizable monomers.
[0013] Preferably, the heterocyclic amine template molecular imprinting polymer is obtained by using a heterocyclic amine compound as a template molecule, a carboxyl group-containing polymerization monomer as a functional monomer, and a cross-linking monomer as a cross-linking agent, and performing a polymerization reaction by a reversible addition-fragmentation chain transfer polymerization method under the action of a chain transfer agent and an initiator, and then removing the template molecule from the polymer obtained by the polymerization reaction; the carboxyl group-containing polymerization monomer has at least one olefinic carbon-carbon unsaturated double bond; and the cross-linking monomer has at least two olefinic carbon-carbon unsaturated double bonds.
[0014] Preferably, the heterocyclic amine compound is a halogen base and / or 9H-pyrido[2,3-b]indole. Preferably, the carboxyl-containing polymer monomer is methylene succinic acid and / or methacrylic acid. Preferably, the cross-linking monomer is ethylene glycol dimethacrylate. Preferably, the chain transfer agent is dithiobenzoic acid (4-cyanovaleric acid) ester. Preferably, the initiator is an azo initiator. For example, the azo initiator is azobisisobutyronitrile or azobiscyanovaleric acid.
[0015] Preferably, the hydrophilic polymer segment is formed by using magnetic particles coated with heterocyclic amine template molecular imprinting polymer as chain transfer agent, and grafting methacryloyl glycylglycine and / or hydroxyethyl methacrylate as polymerization monomers onto the heterocyclic amine template molecular imprinting polymer through reversible addition-fragmentation chain transfer polymerization.
[0016] Preferably, the magnetic particles are ferroferric oxide magnetic particles.
[0017] Preferably, the ferroferric oxide magnetic particles are prepared by co-precipitation of ferrous ions and ferric ions in a liquid alkaline environment.
[0018] Preferably, the molar ratio of ferrous ions to ferric ions is 0.55:1. Preferably, the pH of the liquid alkaline environment is 9 to 10. Preferably, the coprecipitation method comprises the following steps: adjusting the pH of the solution containing ferrous ions and ferric ions to 9 to 10 using an alkaline compound, then heating to 60°C, reacting for 1 hour, then heating to 80°C, and continuing to react for 3 hours.
[0019] Preferably, in the method for preparing the ferroferric oxide magnetic particles, after the reaction is completed, the system after the reaction is completed is subjected to solid-liquid separation, and the solid obtained by the solid-liquid separation is washed to obtain the ferroferric oxide magnetic particles.
[0020] The technical solution adopted by the method for preparing the magnetic heterocyclic amine molecular imprinted composite material of the present invention is:
[0021] (1) coating a heterocyclic amine template molecular imprinting polymer layer on the surface of the magnetic particle to obtain a coating material;
[0022] (2) A chemical grafting method is used to chemically bond a hydrophilic polymer segment to the surface of the coating material; the hydrophilic groups in the hydrophilic polymer segment are carboxyl groups and / or hydroxyl groups.
[0023] The preparation method of the magnetic heterocyclic amine molecular imprinting composite material of the present invention comprises the following steps: firstly, a heterocyclic amine template molecular imprinting polymer is coated on the surface of magnetic particles to obtain a coating material, and then a hydrophilic polymer segment is chemically bonded to the surface of the heterocyclic amine template molecular imprinting polymer by a chemical grafting method to obtain the magnetic heterocyclic amine molecular imprinting composite material. When the magnetic heterocyclic amine molecular imprinting composite material prepared by the present invention is used for adsorbing heterocyclic amine, it has the characteristics of high selectivity, large adsorption capacity, strong anti-interference ability, easy separation, etc., and can be applied to the enrichment and separation of heterocyclic amines in complex aqueous systems.
[0024] When the hydrophilic groups in the hydrophilic polymer chain segments are carboxyl and / or hydroxyl groups, the molecular chain segments have good hydrophilicity and charge, can effectively resist the non-selective adsorption of interfering substances such as proteins, improve the adsorption selectivity of heterocyclic amine molecular imprinting composite materials in aqueous media, and can effectively overcome the defect that the adsorption performance of general molecular imprinting materials in aqueous systems is greatly reduced.
[0025] Preferably, in the method for preparing the magnetic heterocyclic amine molecularly imprinted composite material, the magnetic particles are ferroferric oxide magnetic particles.
[0026] Preferably, in the method for preparing the magnetic heterocyclic amine molecularly imprinted composite material, the ferroferric oxide magnetic particles are prepared by co-precipitation of ferrous ions and ferric ions in a liquid alkaline environment.
[0027] Preferably, in the preparation method of the magnetic heterocyclic amine molecular imprinting composite material, the molar ratio of ferrous ions to ferric ions is 0.55:1. Preferably, in the preparation method of the magnetic heterocyclic amine molecular imprinting composite material, the pH of the liquid alkaline environment is 9 to 10. Preferably, in the preparation method of the magnetic heterocyclic amine molecular imprinting composite material, the coprecipitation method comprises the following steps: using an alkaline compound to adjust the pH of the solution containing ferrous ions and ferric ions to 9 to 10, then heating to 60°C, reacting for 1h, then heating to 80°C, and continuing to react for 3h. Preferably, the ferrous ions are provided by ferrous chloride. Preferably, the ferric ions are provided by ferric chloride.
[0028] Preferably, in the method for preparing the ferroferric oxide magnetic particles, after the reaction is completed, the system after the reaction is completed is subjected to solid-liquid separation, and the solid obtained by the solid-liquid separation is washed to obtain the ferroferric oxide magnetic particles.
[0029] Preferably, the method of coating the surface of magnetic particles with a heterocyclic amine template molecular imprinting polymer layer comprises the following steps: subjecting a reaction system comprising magnetic particles, heterocyclic amine compound template molecules, carboxyl-containing polymerization monomers, cross-linking monomers, chain transfer agents and initiators to polymerization through a reversible addition-fragmentation chain transfer polymerization method, and then removing the template molecules from the polymerization product; the carboxyl-containing polymerization monomers having at least one olefinic carbon-carbon unsaturated double bond; and the cross-linking monomers having at least two olefinic carbon-carbon unsaturated double bonds.
[0030] Preferably, in the preparation method of the magnetic heterocyclic amine molecular imprinting composite material, the heterocyclic amine compound is a hal base and / or 9H-pyrido[2,3-b]indole. When preparing heterocyclic amine template molecular imprinting polymers, using hal base and / or 9H-pyrido[2,3-b]indole as template molecules has the advantages of low price and low toxicity. In addition, hal base and / or 9H-pyrido[2,3-b]indole have similar chemical structures to heterocyclic amines in fried meat foods and cigarette smoke, but are not common heterocyclic amine analytes in heterocyclic amine analysis and evaluation of biological samples. Therefore, using them as templates can overcome the interference with the target heterocyclic amine analyte caused by a small amount of residual template molecules.
[0031] Preferably, in the preparation method of the magnetic heterocyclic amine molecular imprinted composite material, the carboxyl group-containing polymer monomer is methylene succinic acid and / or methacrylic acid. When methylene succinic acid is used as the carboxyl group-containing polymer monomer, since the monomer contains two carboxyl groups, the imprinting site formed by the methylene succinic acid and the template molecule has a stronger imprinting effect on the template molecule, which is more conducive to the adsorption of heterocyclic amines.
[0032] Preferably, in the method for preparing the magnetic heterocyclic amine molecularly imprinted composite material, the cross-linking monomer is ethylene glycol dimethacrylate.
[0033] Preferably, the chain transfer agent used in the method of coating the heterocyclic amine template molecular imprinting polymer layer on the surface of magnetic particles is dithiobenzoic acid (4-cyanovaleric acid) ester.
[0034] Preferably, the initiator used in the method of coating the heterocyclic amine template molecular imprinting polymer layer on the surface of the magnetic particle is an azo initiator. Preferably, the azo initiator used in the method of coating the heterocyclic amine template molecular imprinting polymer layer on the surface of the magnetic particle is azobisisobutyronitrile or azobiscyanovaleric acid.
[0035] Preferably, the molar ratio of the magnetic particles, template molecules, carboxyl-containing polymer monomers, cross-linking monomers, chain transfer agents and initiators used in the method of coating the heterocyclic amine template molecular imprinting polymer layer on the surface of magnetic particles is 1:1:(2-3):(10-15):0.36:(0.12-0.24). When the molar ratio of the magnetic particles, template molecules, carboxyl-containing polymer monomers, cross-linking monomers, chain transfer agents and initiators is within the above range, the formed coating material has an excellent imprinting effect on heterocyclic amines.
[0036] Preferably, the polymerization temperature in the method of coating the surface of the magnetic particle with a heterocyclic amine template molecular imprinting polymer layer is 65-75°C, and the polymerization time is 12-24 hours. When the polymerization temperature and time for preparing the heterocyclic amine template molecular imprinting polymer are within the above range, the monomer conversion can be sufficient and more economical.
[0037] Preferably, the reaction system used in the method of coating the surface of magnetic particles with a heterocyclic amine template molecular imprinting polymer layer also includes an organic solvent. Preferably, the organic solvent is acetonitrile. Preferably, in the reaction system used in the method of coating the surface of magnetic particles with a heterocyclic amine template molecular imprinting polymer layer, 90 mL of the organic solvent is used for every 1 mmol of the heterocyclic amine compound.
[0038] Preferably, the polymerization reaction in the method of coating the surface of magnetic particles with a heterocyclic amine template molecular imprinting polymer layer is carried out under anaerobic conditions. Preferably, the polymerization reaction in the method of coating the surface of magnetic particles with a heterocyclic amine template molecular imprinting polymer layer is carried out in a nitrogen or argon atmosphere.
[0039] Preferably, in the method of coating the surface of magnetic particles with a heterocyclic amine template molecular imprinting polymer layer, after the polymerization reaction is completed, the system after the reaction is cooled to room temperature, and then solid-liquid separation is performed to obtain a product.
[0040] Preferably, the method for removing the template molecule in the product obtained by the polymerization reaction comprises the following steps: washing the product with acetonitrile, methanol, a mixed solution formed by acetic acid and methanol, and methanol in sequence until the template molecule is no longer detected, and then drying to obtain a heterocyclic amine template molecular imprinting polymer.
[0041] Preferably, in the method for removing template molecules from the product obtained by polymerization reaction, the drying is vacuum drying.
[0042] Preferably, in the method for removing the template molecule in the product obtained by the polymerization reaction, in the mixed solution formed by acetic acid and methanol, the volume ratio of the acetic acid to the methanol is 1:(20-30). For example, preferably, in the method for removing the template molecule in the product obtained by the polymerization reaction, in the mixed solution formed by acetic acid and methanol, the volume ratio of the acetic acid to the methanol is 1:20. When the volume ratio of acetic acid to methanol is 1:(20-30), the template molecules can be effectively eluted with little effect on the core magnetic particles.
[0043] Preferably, the method of chemically bonding a hydrophilic polymer segment on the surface of a coating material comprises the following steps: subjecting a reaction system containing a polymerizable monomer and a coating material to a polymerization reaction by a reversible addition-fragmentation chain transfer polymerization method; the polymerizable monomer is methacryloylglycylglycine and / or hydroxyethyl methacrylate.
[0044] Methacryloylglycylglycine and / or hydroxyethyl methacrylate are used as polymerization monomers. The hydrophilic polymer chain segments formed by polymerization have good hydrophilicity and charge, can effectively resist the non-selective adsorption of interfering substances such as proteins, and improve the adsorption selectivity of heterocyclic amines.
[0045] Preferably, in the method of chemically bonding the hydrophilic polymer segments on the surface of the coating material, the amount of the polymerized monomer used per 200g of the coating material is 18 to 54 mol. The amount of the polymerized monomer used per 200g of the coating material is 18 to 54 mol, and the hydrophilic polymer segments formed by polymerization have a suitable segment length, which can effectively resist the non-selective adsorption of interfering substances such as proteins, etc., and improve the adsorption selectivity of heterocyclic amines.
[0046] Preferably, the reaction system used in the method of chemically bonding the hydrophilic polymer segments on the surface of the coating material consists of polymer monomers, coating materials, chain transfer agents, initiators and solvents.
[0047] Preferably, the polymerization reaction in the method of chemically bonding the hydrophilic polymeric segments on the surface of the coating material is carried out under anaerobic conditions. Preferably, the polymerization reaction in the method of chemically bonding the hydrophilic polymeric segments on the surface of the coating material is carried out in a nitrogen atmosphere.
[0048] Preferably, the solvent in the reaction system used in the method of chemically bonding a hydrophilic polymer segment on the surface of the coating material is dioxane or an ethanol aqueous solution. Preferably, the ethanol aqueous solution is a mixture of ethanol and water in a volume ratio of 1:1. Preferably, the chain transfer agent used in the method of chemically bonding a hydrophilic polymer segment on the surface of the coating material is dithiobenzoic acid (4-cyanovaleric acid) ester. Preferably, the initiator used in the method of chemically bonding a hydrophilic polymer segment on the surface of the coating material is an azo initiator. Preferably, the azo initiator used in the method of chemically bonding a hydrophilic polymer segment on the surface of the coating material is azobisisobutyronitrile or azobiscyanovaleric acid. Preferably, the molar ratio of the polymerization monomer, chain transfer agent and initiator used in the method of chemically bonding a hydrophilic polymer segment on the surface of the coating material is (18-54):0.036:0.018.
[0049] Preferably, the temperature of the polymerization reaction in the method of chemically bonding the hydrophilic polymer segment on the surface of the coating material is 65-75° C., and the polymerization reaction time is 12-24 hours. For example, the temperature of the polymerization reaction in the method of chemically bonding the hydrophilic polymer segment on the surface of the coating material is 70° C., and the polymerization reaction time is 12 hours.
[0050] Preferably, in the method of chemically bonding the hydrophilic polymer segments on the surface of the coating material, after the polymerization reaction is completed, the system after the reaction is cooled to room temperature and then solid-liquid separation is performed, and the solid obtained by solid-liquid separation is the magnetic heterocyclic amine molecular imprinting composite material.
[0051] The technical solution adopted by the application of the magnetic heterocyclic amine molecular imprinted composite material of the present invention in adsorbing heterocyclic amine in an aqueous system is:
[0052] Application of the magnetic heterocyclic amine molecularly imprinted composite material as described above or the magnetic heterocyclic amine molecularly imprinted composite material prepared by the preparation method of the magnetic heterocyclic amine molecularly imprinted composite material as described above in adsorbing heterocyclic amine in an aqueous system.
[0053] When the magnetic heterocyclic amine molecular imprinting composite material as described above or the magnetic heterocyclic amine molecular imprinting composite material prepared by the preparation method of the magnetic heterocyclic amine molecular imprinting composite material as described above is used to adsorb heterocyclic amines in an aqueous system, it has high selective adsorption, can improve the recognition performance of heterocyclic amine molecules in complex aqueous media, and has the characteristics of easy separation, and is suitable for the adsorption and analysis of heterocyclic amines in aqueous biological samples such as urine.
[0054] Preferably, the aqueous system is urine or blood. The magnetic heterocyclic amine molecular imprinting composite material of the present invention can efficiently and selectively adsorb heterocyclic amines in biological samples such as urine and blood, and is of great significance for the analysis and detection of heterocyclic amines in biological samples.
[0055] It is understandable that when the magnetic heterocyclic amine molecular imprinting composite material is used to adsorb heterocyclic amines in an aqueous system, the magnetic heterocyclic amine molecular imprinting composite material can be directly mixed with the aqueous system containing heterocyclic amines, or the magnetic heterocyclic amine molecular imprinting composite material can be loaded into an adsorption column as an adsorbent filler and then the adsorption column is used to treat the aqueous system containing heterocyclic amines.
[0056] Preferably, the aqueous system is urine; the application comprises the following steps: firstly subjecting the urine to an acid hydrolysis treatment, then adjusting the pH of the acid hydrolyzed urine to neutral to obtain pre-treated urine, and then using the magnetic heterocyclic amine molecular imprinting composite material to adsorb the heterocyclic amine in the pre-treated urine.
[0057] Preferably, before using the magnetic heterocyclic amine molecular imprinting composite material to adsorb heterocyclic amines in pre-treatment urine, the magnetic heterocyclic amine molecular imprinting composite material is first soaked in methanol, and then the soaked magnetic heterocyclic amine molecular imprinting composite material is used to adsorb heterocyclic amines in pre-treatment urine.
[0058] Preferably, after the heterocyclic amine in the pre-treated urine is adsorbed by the magnetic heterocyclic amine molecular imprinting composite material, the magnetic heterocyclic amine molecular imprinting composite material adsorbed with heterocyclic amine is firstly eluted with water and methanol in sequence to remove interferences, and then the heterocyclic amine in the magnetic heterocyclic amine molecular imprinting composite material adsorbed with heterocyclic amine is eluted with a heterocyclic amine eluent.
[0059] Preferably, when water and methanol are used to elute the magnetic heterocyclic amine molecularly imprinted composite material adsorbed with heterocyclic amine, the volume of water and methanol used is 5 mL for every 150 mg of the magnetic heterocyclic amine molecularly imprinted composite material.
[0060] Preferably, the heterocyclic amine eluent is a mixture of ammonia water and methanol. Preferably, the volume ratio of ammonia water to methanol is 1:19. Preferably, the mass fraction of ammonia water is 25-30%. For example, the mass fraction of ammonia water is 30%.
[0061] It can be understood that after the heterocyclic amines in the urine are adsorbed by the magnetic heterocyclic amine molecular imprinting composite material, the separation and enrichment of the heterocyclic amines in the urine is completed, and after the heterocyclic amines adsorbed in the magnetic heterocyclic amine molecular imprinting composite material are eluted, the content of the heterocyclic amines can be analyzed and tested with reference to the existing technology. DETAILED DESCRIPTION
[0062] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0063] 1. The specific embodiments of the magnetic heterocyclic amine molecular imprinted composite material of the present invention are as follows:
[0064] The magnetic heterocyclic amine molecularly imprinted composite material of Examples 1-12 comprises a magnetic particle core and a heterocyclic amine template molecularly imprinted polymer shell coated on the surface of the magnetic particle core, and a hydrophilic polymer segment is grafted on the surface of the molecularly imprinted polymer shell.
[0065] The magnetic particles are ferroferric oxide magnetic particles, which are prepared by co-precipitation of ferrous ions and ferric ions in a liquid alkaline environment.
[0066] The heterocyclic amine template molecular imprinting polymer is obtained by using heterocyclic amine compounds as template molecules, carboxyl-containing polymerization monomers as functional monomers, cross-linking monomer ethylene glycol dimethacrylate as cross-linking agent, and carrying out polymerization reaction through reversible addition-fragmentation chain transfer polymerization under the action of chain transfer agent dithiobenzoic acid (4-cyanovaleric acid) ester and initiator azobisisobutyronitrile, and then removing the template molecules in the polymer obtained by the polymerization reaction.
[0067] The hydrophilic polymer chain segment is formed by using magnetic particles coated with heterocyclic amine template molecular imprinting polymer as a chain transfer agent to graft polymer monomers (methacryloyl glycylglycine and / or hydroxyethyl methacrylate) onto the core through a reversible addition-fragmentation chain transfer polymerization reaction.
[0068] In Examples 1-12, the template molecules and functional monomers used in preparing heterocyclic amine template molecular imprinted polymers and the types of polymer monomers used in constructing hydrophilic polymer segments are shown in Table 1. In Table 1, methacryloylglycylglycine is represented by MAGG, and hydroxyethyl methacrylate is represented by HEMA.
[0069] Table 1 Types of template molecules and functional monomers used in preparing heterocyclic amine template molecular imprinting polymers and types of polymer monomers used in constructing hydrophilic polymer segments in Examples 1-12
[0070] Imprinted composites Template molecule Functional monomer Polymerization monomer Example 1 Halogen Methylene Succinic Acid MAGG Example 2 Halogen Methylene Succinic Acid MAGG Example 3 Halogen Methylene Succinic Acid MAGG Example 4 Halogen Methacrylic acid MAGG Example 5 9H-Pyrido[2,3-b]indole Methylene Succinic Acid MAGG Example 6 9H-Pyrido[2,3-b]indole Methacrylic acid MAGG Example 7 Halogen Methylene Succinic Acid HEMA Example 8 Halogen Methylene Succinic Acid HEMA Example 9 Halogen Methylene Succinic Acid HEMA Example 10 Halogen Methacrylic acid HEMA Embodiment 11 9H-Pyrido[2,3-b]indole Methylene Succinic Acid HEMA Example 12 9H-Pyrido[2,3-b]indole Methacrylic acid HEMA
[0071] 2. The specific embodiment of the preparation method of the magnetic heterocyclic amine molecularly imprinted composite material of the present invention is as follows:
[0072] The preparation method of the magnetic heterocyclic amine molecular imprinted composite material of Examples 13-24 comprises the following steps:
[0073] (1) Ferrous chloride and ferric chloride are dissolved in water at a molar ratio of ferrous ion to ferric ion of 0.55:1, and then potassium hydroxide is used to adjust the pH to 9-10. After reacting at 60° C. for 1 hour, the temperature is raised to 80° C. and the reaction is continued for 3 hours. The system after the reaction is filtered, and the filtered solid is washed to obtain black microparticles of ferroferric oxide magnetic particles.
[0074] (2) 1 mmol of ferroferric oxide magnetic particles, 1 mmol of heterocyclic amine compounds, 3 mmol of carboxyl group-containing polymerization monomers, 15 mmol of cross-linking monomers ethylene glycol dimethacrylate, 0.36 mmol of chain transfer agent dithiobenzoic acid (4-cyanovaleric acid) ester, 0.24 mmol of azo initiator azobisisobutyronitrile (AIBN) and 90 mL of acetonitrile solvent were added to the reaction container in sequence, and then the system in the reaction container was stirred, and then nitrogen was filled into the reaction container to remove oxygen, and then the reaction container was sealed. The reaction system in the reaction container was then heated to 70°C to perform a reversible addition-fragmentation chain transfer polymerization reaction for 12 hours. After the reaction was completed, the system after the reaction was cooled to room temperature and then centrifuged. The solid obtained by centrifugation was then washed with acetonitrile, methanol, a mixed solution of acetic acid and methanol with a volume ratio of 1:20, and methanol in sequence until the template molecule (heterocyclic amine compound) was no longer detected, and then vacuum dried to obtain a coating material.
[0075] (3) 200 mg of coating material, appropriate amount of polymerizable monomer, 0.036 mmol of chain transfer agent dithiobenzoic acid (4-cyanovaleric acid) ester, 0.018 mmol of initiator azobiscyanovaleric acid and appropriate amount of solvent dioxane are added to the reaction container in sequence, and then the system in the reaction container is stirred, and then nitrogen is filled into the reaction container to remove oxygen, and then the reaction container is sealed. The reaction system in the reaction container is then heated to 70° C., so that the polymerizable monomer is grafted onto the heterocyclic amine template molecular imprinting polymer through a reversible addition-fragmentation chain transfer polymerization reaction, and the polymerization reaction time is 12 hours. After the polymerization reaction is completed, the system after the reaction is cooled to room temperature, and then centrifuged. The solid obtained by centrifugation is the magnetic heterocyclic amine molecular imprinting composite material.
[0076] Among them, the types of heterocyclic amine compounds and carboxyl-containing polymer monomers used in step (2) and the types, amounts and amounts of solvents used in step (3) in the preparation methods of magnetic heterocyclic amine molecularly imprinted composite materials of Examples 13-24 are shown in Table 2. In Table 2, methacryloyl glycylglycine is represented by MAGG, and hydroxyethyl methacrylate is represented by HEMA.
[0077] In Example 14 and Example 16, the coating materials obtained in step (2) are marked as Fe3O4-MIP-1 and Fe3O4-MIP-2, respectively.
[0078] The preparation methods of the magnetic heterocyclic amine molecularly imprinted composite materials of Examples 13-24 are respectively the preparation methods of the magnetic heterocyclic amine molecularly imprinted composite materials of Examples 1-12.
[0079] Table 2 Heterocyclic amine compounds and carboxyl-containing polymers used in step (2) in the preparation method of magnetic heterocyclic amine molecularly imprinted composite materials of Examples 13-24
[0080] The type of monomer and the type, amount and amount of the polymerization monomer used in step (3)
[0081]
[0082] Comparative Example 1
[0083] The difference between the preparation method of the composite material of this comparative example and the preparation method of the magnetic heterocyclic amine molecular imprinting composite material of Example 14 is that no heterocyclic amine compound is added in step (2). The coated material obtained in step (2) is marked as Fe3O4-CP-1. The composite material prepared in this comparative example is a non-imprinting composite material, marked as Fe3O4-CP-1-PMAGG-2.
[0084] Comparative Example 2
[0085] The difference between the preparation method of the composite material of this comparative example and the preparation method of the magnetic heterocyclic amine molecular imprinting composite material of Example 16 is that no heterocyclic amine compound is added in step (2). The coated material obtained in step (2) is marked as Fe3O4-CP-2. The composite material prepared in this comparative example is a non-imprinting composite material, marked as Fe3O4-CP-2-PMAGG-2.
[0086] Comparative Example 3
[0087] The preparation method of the composite material of this comparative example is different from the preparation method of the magnetic heterocyclic amine molecular imprinted composite material of Example 20 in that no heterocyclic amine compound is added in step (2). The composite material prepared in this comparative example is a non-imprinted composite material, marked as Fe3O4-CP-1-PHEMA-2.
[0088] Comparative Example 4
[0089] The preparation method of the composite material of this comparative example is different from the preparation method of the magnetic heterocyclic amine molecularly imprinted composite material of Example 22 in that no heterocyclic amine compound is added in step (2). The composite material prepared in this comparative example is a non-imprinted composite material, marked as Fe3O4-CP-2-PHEMA-2.
[0090] Experimental Example 1
[0091] In order to investigate whether the molecular imprinting coating material has good adsorption performance for the template molecule and the target analyte heterocyclic amine Harman, the coating material prepared in Example 14 (labeled as Fe3O4-MIP-1) and the non-imprinting coating material prepared in Comparative Example 1 (labeled as Fe3O4-CP-1) were tested for their adsorption performance for Harman base or Harman in organic solvents acetonitrile and water. The experimental method is as follows: 10 mg of the coating material (Fe3O4-MIP-1 or Fe3O4-CP-1) was placed in a volume of 2 mL and a concentration of 0.10 mmol / L Harman base solution or Harman solution. After oscillating and adsorbing for 12 hours, the absorbance was detected, and the adsorption amount was calculated based on the absorbance change. The experimental results are shown in Table 3.
[0092] Table 3 Test results of the adsorption performance of different composite materials on Harman base or Harman in organic solvents acetonitrile and water
[0093]
[0094] The results show that in organic solvents, the adsorption amounts of Hal base by Fe3O4-MIP-1 and Fe3O4-CP-1 are 13.0 and 3.4 μmol / g, respectively. The adsorption amount of Hal base by Fe3O4-MIP-1 is significantly higher than that by Fe3O4-CP-1, and the imprinting factor is as high as 3.8, indicating that the prepared Fe3O4-MIP-1 has excellent molecular recognition performance for Hal base in organic solution, which is closely related to the use of Hal base as a template for preparation. There are a large number of imprinting sites in the coating material, which shows excellent adsorption performance for the template molecule Hal base in the organic solvent system.
[0095] Since Harman is widely present in cigarette smoke, it also exists in the body fluids of cigarette consumers. In order to verify whether the coating material prepared with Harman base as template has good adsorption for the target analyte Harman, the adsorption performance of the coating material for the target analyte Harman in organic solvents and water was investigated.
[0096] The results show that in organic solvents, the adsorption amounts of Harman by Fe3O4-MIP-1 and Fe3O4-CP-1 are 8.4 and 2.0 μmol / g, respectively. The adsorption amount of Harman by Fe3O4-MIP-1 is also significantly higher than that by Fe3O4-CP-1. That is, the molecular imprinting material prepared with Hal base also shows obvious adsorption selectivity for the target analyte Harman, and the imprinting factor is as high as 4.2, indicating that the imprinting site formed by Hal base is also highly selective for its heterocyclic amine Harman. That is, the molecular imprinting material prepared with Hal base has good adsorption performance for the target analyte heterocyclic amine Harman.
[0097] In aqueous systems, the adsorption amounts of Harman by Fe3O4-MIP-1 and Fe3O4-CP-1 were 9.6 and 6.6 μmol / g, respectively. The adsorption selectivity of the coating material was significantly reduced, and the imprinting factor was only 1.5, indicating that the adsorption of Harman by Fe3O4-MIP-1 in aqueous solution was mainly non-specific adsorption, such as hydrophobic interaction, electrostatic effect, etc. The imprinting factor was reduced from 4.2 in organic systems to 1.5 in aqueous systems, indicating that the molecular recognition performance of Fe3O4-MIP-1, a coating material without grafted hydrophilic polymer segments, in aqueous systems was greatly reduced.
[0098] Experimental Example 2
[0099] In order to investigate the adsorption performance of magnetic heterocyclic amine molecular imprinting composites on target analyte Harman, the adsorption performance of magnetic heterocyclic amine molecular imprinting composites Fe3O4-MIP-1-PMAGG-2, Fe3O4-MIP-2-PMAGG-2, Fe3O4-MIP-1-PHEMA-2 and control composites Fe3O4-CP-1-PMAGG-2, Fe3O4-CP-2-PMAGG-2, Fe3O4-CP-1-PHEMA-2 on Harman in water was tested respectively. The experimental method is as follows: 10 mg of magnetic heterocyclic amine molecular imprinting composites or control composites are placed in a volume of 2 mL of 0.10 mmol / L Harman base solution or Harman solution, and after oscillation adsorption for 12 hours, the absorbance is detected, and the adsorption amount is calculated based on the absorbance change. The experimental results are shown in Table 4.
[0100] Table 4 Test results of Harman adsorption performance of different composite materials in water
[0101] Composite Materials Adsorption capacity μmol / g Imprinting Factors <![CDATA[Fe3O4-MIP-1-PMAGG-2]]> 9.0 4.5 <![CDATA[Fe3O4-CP-1-PMAGG-2]]> 2.0 / <![CDATA[Fe3O4-MIP-2-PMAGG-2]]> 8.1 3.7 <![CDATA[Fe3O4-CP-2-PMAGG-2]]> 2.2 / <![CDATA[Fe3O4-MIP-1-PHEMA-2]]> 7.8 4.1 <![CDATA[Fe3O4-CP-1-PHEMA-2]]> 1.9 /
[0102] The results showed that in aqueous system, the adsorption capacity of Fe3O4-MIP-1-PMAGG-2, Fe3O4-MIP-2-PMAGG-2, Fe3O4-CP-1-PMAGG-2 and Fe3O4-CP-2-PMAGG-2 for Harman were 9.0, 8.1, 2.0 and 2.2 μmol / g, respectively. Compared with the non-imprinted material (control composite material), the magnetic heterocyclic amine molecular imprinted composite materials with three-layer structure had higher adsorption capacity for Harman in aqueous solution, which were significantly higher than the adsorption capacity of non-imprinted composite materials Fe3O4-CP-1-PMAGG-2 and Fe3O4-CP-2-PMAGG-2, and the imprinting factors were 4.5 and 3.7, respectively.
[0103] Compared with the magnetic heterocyclic amine molecular imprinting composite material (coating material) without grafting hydrophilic polymer segments, the prepared magnetic heterocyclic amine molecular imprinting composite material has significantly improved adsorption selectivity for Harman in aqueous solution after using methacryloylglycylglycine as a polymerization monomer to prepare hydrophilic polymer segments. For example, the imprinting factor of the coating material Fe3O4-MIP-1 for adsorption of Harman in an aqueous system is 1.5 (as shown in Table 3), and the imprinting factor of the magnetic heterocyclic amine molecular imprinting composite material Fe3O4-MIP-1-PMAGG-2 for adsorption of Harman in an aqueous system after grafting hydrophilic polymer segments is increased to 4.5, indicating that after the introduction of hydrophilic polymer segments, the molecular recognition performance of the magnetic heterocyclic amine molecular imprinting composite material is significantly improved. Therefore, the hydrophilic polymer segments on the surface of the magnetic heterocyclic amine molecular imprinting composite material can effectively improve the adsorption selectivity of the molecular imprinting polymer in an aqueous medium, and can effectively overcome the defect that the adsorption selectivity of general molecular imprinting materials in an aqueous system is greatly reduced.
[0104] The adsorption amount of Harman in aqueous solution of the magnetic heterocyclic amine molecular imprinting composite Fe3O4-MIP-1-PMAGG-2 prepared with methylene succinic acid as the functional monomer (9.0 μmol / g) is higher than that of the magnetic heterocyclic amine molecular imprinting composite Fe3O4-MIP-1-PMAGG-2 prepared with methacrylic acid as the functional monomer (8.1 μmol / g). The imprinting factor of the former (4.5) is also higher than that of the latter (3.7), indicating that the adsorption selectivity of the magnetic heterocyclic amine molecular imprinting composite prepared with methylene succinic acid as the carboxyl-containing polymerization monomer is better than that of the magnetic heterocyclic amine molecular imprinting composite prepared with methacrylic acid as the carboxyl-containing polymerization monomer. This may be related to the fact that there are more carboxyl groups in methylene succinic acid, which makes the imprinting sites in the final composite more effective.
[0105] In addition, the magnetic heterocyclic amine molecular imprinted composite material Fe3O4-MIP-1-PHEMA-2 prepared with hydroxyethyl methacrylate as the polymerization monomer also has good adsorption performance for Harman in aqueous solution, and the imprinting factor reaches 4.1.
[0106] Experimental Example 3
[0107] The magnetic heterocyclic amine molecular imprinting composite material Fe3O4-MIP-1-PMAGG-2 is used for the detection of Harman in urine, which specifically includes the following steps:
[0108] (1) Urine pretreatment: 1 mL of urine was mixed with 100 μL of hydrochloric acid solution (12 mol / L) and heated at 70°C for 3 h to acidify the urine and free the heterocyclic amines in the urine. The urine was then cooled and neutralized with sodium hydroxide solution to obtain pretreated urine.
[0109] (2) Separation and enrichment of heterocyclic amines in urine: 150 mg of the magnetic heterocyclic amine molecular imprinting composite material Fe3O4-MIP-1-PMAGG-2 was soaked in methanol, and then the soaked Fe3O4-MIP-1-PMAGG-2 was loaded into a small column to prepare a solid phase extraction small column. The pretreated urine obtained in step (1) was then added to the solid phase extraction small column, and the heterocyclic amines in the urine were adsorbed by the magnetic heterocyclic amine molecular imprinting composite material to achieve the separation and enrichment of heterocyclic amines (Harman) in urine.
[0110] (3) Analysis and testing: 5 mL of water and 5 mL of methanol were used to elute the solid phase extraction column after separation and enrichment to remove interferences, and then 10 mL of a solution formed by ammonia water (mass fraction of 30%) and methanol in a volume ratio of 1:19 was used to elute the heterocyclic amines enriched in the solid phase extraction column. The eluate was collected and concentrated to 1.0 mL using nitrogen blowing. Finally, the heterocyclic amine (Harman) content in the eluate was analyzed by HPLC-MS / MS. The analysis results showed that the heterocyclic amine (Harman) content in the eluate was 0.85 ng / mL.
[0111] The chromatographic column used in the HPLC-MS / MS analysis was a Zorbax Eclipse Plus C18 column (3.0 mm×100 mm, 1.8 μm), the mobile phase was 0.1% acetic acid solution (A) and acetonitrile (B) by mass fraction, the flow rate of the mobile phase was 0.30 mL / min, and the elution gradient was: 0-2 min, 5% B; 2-20 min, 35% B; 21-24 min, 100% B.
Claims
1. A magnetic heterocyclic amine molecular imprinting composite material, characterized in that: The invention comprises a magnetic particle core and a heterocyclic amine template molecular imprinting polymer shell coated on the surface of the magnetic particle core, wherein the surface of the molecular imprinting polymer shell is chemically bonded with a hydrophilic polymer segment; the hydrophilic polymer segment is formed by polymerization reaction using methacryloylglycylglycine as a polymer monomer; the heterocyclic amine template molecular imprinting polymer is obtained by polymerization reaction using heterocyclic amine compounds as template molecules and carboxyl-containing polymer monomers as functional monomers, and then removing the template molecules from the polymer obtained by the polymerization reaction; the carboxyl-containing polymer monomer is methylene succinic acid.
2. The magnetic heterocyclic amine molecularly imprinted composite material according to claim 1, characterized in that: The polymerization reaction is carried out by a reversible addition-fragmentation chain transfer polymerization method with a cross-linking monomer as a cross-linking agent under the action of a chain transfer agent and an initiator; the cross-linking monomer has at least two or more olefinic carbon-carbon unsaturated double bonds.
3. The magnetic heterocyclic amine molecularly imprinted composite material according to claim 2, characterized in that: The heterocyclic amine compound is a Hal base and / or 9H-pyrido[2,3-b]indole.
4. The magnetic heterocyclic amine molecularly imprinted composite material according to claim 2, characterized in that: The cross-linking monomer is ethylene glycol dimethacrylate; the chain transfer agent is dithiobenzoic acid (4-cyanovaleric acid) ester; and the initiator is an azo initiator.
5. The magnetic heterocyclic amine molecularly imprinted composite material according to claim 1, characterized in that: The magnetic particles are ferroferric oxide magnetic particles.
6. The method for preparing the magnetic heterocyclic amine molecularly imprinted composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) coating the surface of magnetic particles with a heterocyclic amine template molecular imprinting polymer layer to obtain a coating material; (2) The chemical grafting method is used to chemically bond the hydrophilic polymer chain segments on the surface of the coating material.
7. The method for preparing the magnetic heterocyclic amine molecularly imprinted composite material according to claim 6, characterized in that: The method for coating a heterocyclic amine template molecular imprinting polymer layer on the surface of magnetic particles comprises the following steps: subjecting a reaction system including magnetic particles, heterocyclic amine compound template molecules, carboxyl group-containing polymerization monomers, cross-linking monomers, chain transfer agents and initiators to polymerization through a reversible addition-fragmentation chain transfer polymerization method, and then removing the template molecules from the polymerization product; the cross-linking monomers have at least two or more olefinic carbon-carbon unsaturated double bonds.
8. The method for preparing the magnetic heterocyclic amine molecularly imprinted composite material according to claim 7, characterized in that: The heterocyclic amine compound is a Hal base and / or 9H-pyrido[2,3-b]indole.
9. The method for preparing the magnetic heterocyclic amine molecularly imprinted composite material according to claim 7, characterized in that: The cross-linking monomer is ethylene glycol dimethacrylate; the chain transfer agent is dithiobenzoic acid (4-cyanovaleric acid) ester; and the initiator is an azo initiator.
10. The method for preparing the magnetic heterocyclic amine molecularly imprinted composite material according to claim 7, characterized in that: In the method of coating the surface of magnetic particles with a heterocyclic amine template molecular imprinting polymer layer, the molar ratio of the magnetic particles, template molecules, carboxyl-containing polymerization monomers, cross-linking monomers, chain transfer agents and initiators is 1:1:(2-3):(10-15):0.36:(0.12-0.24).
11. The method for preparing the magnetic heterocyclic amine molecularly imprinted composite material according to claim 7, characterized in that: In the method of coating the surface of magnetic particles with a heterocyclic amine template molecular imprinting polymer layer, the polymerization reaction temperature is 65-75° C. and the polymerization reaction time is 12-24 hours.
12. The method for preparing the magnetic heterocyclic amine molecularly imprinted composite material according to any one of claims 7 to 11, characterized in that: The method for chemically bonding a hydrophilic polymer segment on the surface of a coating material comprises the following steps: subjecting a reaction system containing a polymer monomer and a coating material to a polymerization reaction by a reversible addition-fragmentation chain transfer polymerization method; the polymer monomer is methacryloylglycylglycine.
13. The method for preparing the magnetic heterocyclic amine molecularly imprinted composite material according to claim 12, characterized in that: The amount of the polymerized monomer used per 200 g of the coating material is 18 to 54 mol.
14. The method for preparing the magnetic heterocyclic amine molecularly imprinted composite material according to claim 12, characterized in that: In the method of chemically bonding a hydrophilic polymer segment on the surface of a coating material, the reaction system used is composed of a polymer monomer, a coating material, a chain transfer agent, an initiator and a solvent, wherein the chain transfer agent is dithiobenzoic acid (4-cyanovaleric acid) ester, and the initiator is an azo initiator. The molar ratio of the polymer monomer, the chain transfer agent and the initiator in the reaction system is (18~54):0.036:0.
018.
15. The method for preparing the magnetic heterocyclic amine molecularly imprinted composite material according to claim 12, characterized in that: In the method of chemically bonding the hydrophilic polymer segments on the surface of the coating material, the polymerization reaction temperature is 65-75° C. and the polymerization reaction time is 12-24 hours.
16. The method for preparing the magnetic heterocyclic amine molecularly imprinted composite material according to any one of claims 6 to 11, characterized in that: The magnetic particles are ferroferric oxide magnetic particles.
17. Use of the magnetic heterocyclic amine molecularly imprinted composite material according to any one of claims 1 to 5 or the magnetic heterocyclic amine molecularly imprinted composite material prepared by the preparation method of the magnetic heterocyclic amine molecularly imprinted composite material according to any one of claims 6 to 16 in adsorbing heterocyclic amine in an aqueous system.
18. The use according to claim 17, characterized in that The aqueous system is urine or blood.
19. The use according to claim 17 or 18, characterized in that The aqueous system is urine; the application comprises the following steps: firstly, the urine is subjected to acid hydrolysis treatment, and then the pH of the acid hydrolyzed urine is adjusted to neutral to obtain pre-treated urine, and then the magnetic heterocyclic amine molecular imprinting composite material is used to adsorb the heterocyclic amine in the pre-treated urine.
Citation Information
Patent Citations
Surface-hydrophilic molecularly imprinted polymer microsphere and preparation method thereof
CN102059104A
Magnetic heterocyclic amine molecularly imprinted polymer and preparation method thereof
CN103467654A